2016
DOI: 10.6061/clinics/2016(12)05
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of embolization for periuterine varices involving chronic pelvic pain secondary to pelvic congestion syndrome

Abstract: OBJECTIVES:To evaluate the clinical response and success rate after periuterine varices embolization in patients with chronic pelvic pain secondary to pelvic congestion syndrome and to report the safety of endovascular treatment and its rate of complications.METHODS:Retrospective cohort of patients undergoing endovascular treatment of pelvic congestion syndrome in our department from January 2012 to November 2015. Data were analyzed based on patient background, imaging findings, embolized veins, rate of compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…Despite previous publications suggesting ovarian vein reflux is largely responsible for PCS 21,22 , our data shows that embolisation of one or both internal iliac veins is essential for managing this condition, as all patients required treatment of at least one or more of its tributaries. Transvaginal venous duplex ultrasound using the Holdstock-Harrison and Holdstock-White protocols demonstrates that many women presenting with lower limb varicose veins arises from reflux of pelvic veins.…”
Section: Discussioncontrasting
confidence: 92%
“…Despite previous publications suggesting ovarian vein reflux is largely responsible for PCS 21,22 , our data shows that embolisation of one or both internal iliac veins is essential for managing this condition, as all patients required treatment of at least one or more of its tributaries. Transvaginal venous duplex ultrasound using the Holdstock-Harrison and Holdstock-White protocols demonstrates that many women presenting with lower limb varicose veins arises from reflux of pelvic veins.…”
Section: Discussioncontrasting
confidence: 92%
“…Of note, the authors reported that seven patients (31.8%) were postmenopausal upon inclusion but did not clarify how menopausal status had been assessed. No significant difference in therapy success was reported between pre- and postmenopausal patients [ 15 ]. Similarly, the largest retrospective study of endovascular treatment of PCS to date included 202 patients with a mean age of 43.5 years (range 27–57 years), and is also likely to have included postmenopausal patients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCS, however, has been primarily associated with the premenopausal state and postmenopausal remission of symptoms has been termed a hallmark of PCS [ 6 , 14 ]. This perception is challenged by recent, sporadic observations of newly diagnosed symptomatic postmenopausal patients with pelvic or vulvovaginal varicose veins, suggesting that limiting diagnostic criteria to premenopausal patients may prevent a subset of patients to access available therapeutic options [ 15 , 16 ]. To address this potential diagnostic gap, we thereby present the first systematic report on a symptomatic postmenopausal PCS patient who experienced a full alleviation of symptoms after receiving the standard-of-care usually applied to respective premenopausal patients.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Pelvic varicosities and CPP are typical findings of PVC, although women diagnosed with pelvic varicose veins may be asymptomatic, constituting a diagnostic challenge for gynecologists investigating CPP. 6,8 Multiparity is a constant in patients with PVC, with complaints of dysmenorrhea and exacerbation of symptoms during or after coitus and when standing for long periods. The origin of PVC is very probably multifactorial and two factors appear to play an important role in genesis of cases.…”
Section: Discussionmentioning
confidence: 99%
“…16 Although several different diagnostic methods are under analysis for their potential to identify and diagnose PVC, including transvaginal ultrasound, computed tomography, and magnetic resonance, 4,6 angiography is still the gold standard, for diagnosis both of PVC and of anatomic anomalies of the IVC and iliac veins, because it enables assessment of the different flow patterns and also allows treatment by coil embolization or decompression of venous trunks by stenting during the same intervention. 4,8,17 Certain angiographic criteria should be present to confirm a diagnosis of PVC, specifically: reflux demonstrated by proximal injection of contrast into the ovarian vein with filling of the distal ovarian venous plexus, incompetent pelvic veins with 5 to 10 mm diameters, flow stasis in the ovarian venous plexus, with visualization of pelvic veins at the median line, vulvovaginal, and proximal thighs. 6,17 There is no standardized treatment for PVC.…”
Section: Discussionmentioning
confidence: 99%